Development of Recipes by Mathematical Modeling - Seidykh, Olga; Makovetska, Svetlana (My University, 2013)
This paper shows the benefits of computer-aided design formulas to create functional foods and their possible regulation by altering the chemical composition of the individual components value , taking into account properties. Designing food structure optimal methods of mathematical modeling will reduce the financial and time costs of developing food products to respond to the changing needs of the human body in a technological society, expand the product range of functional and health-care setting, which focused on individual food groups
Keywords: mathematical modeling; recipe compositions have Excel «Search solutions»; рецептурні композиції; засіб Excel «Поиск решения»; математичне моделювання; рецептурные композиции; математическое моделирование; средство Excel «Поиск решения»; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки